Prawo do milczenia w procesie karnym (w związku z pracą „Samooskarżenie w świetle prawa karnego") - Jeż-Ludwichowska, Maria (Wydział Prawa i Administracji UAM, 1985)
The following article is a text polemising with the work by Z. Sobolewski titled Self-accusation in the ligth of penal law. The great controversy over the work, makes a brief discussion on it, one which would still touch upon all the controversial issues, very difficult indeed. Therefore the author has concentrated on what she considered most vital in the work, namely, the limits to the „Right to remain silent". And quite rightly, as the right to refuse to give evidence is one of the most difficult problems in criminal proceedings, one, at the same time, of its most sore points. Hence the work by Z. Sobolewski has met with great interest, not only among lawyers. Hence it was noticed by the author and hence the above polemic remarks.
The Right to Refuse to Give Evidence in Criminal Proceedings in Connection with the Work: „Self-Accusation in the Light of Penal Law"